Numerical Analysis of Draft Tube Vortices of Francis Turbine with Experimental Validation - Basnet, S.; Bijukche, P.L.; Shrestha, P.; Chitrakar, S.; Adhikari, R.P. (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Although hydraulic turbines are designed for the Best Efficiency Point (BEP), turbines are mostly operated at off-designed conditions due to variation in flow and load. The turbine’s efficiency decreases during the operation away from BEP. Draft tube vortices, generated while operating away from BEP are one of the causes for the decrease in efficiency, enhancing vibration problems, as well as the deterioration of the turbine in some cases. The objective of present study is to model and analyze the vortex rope formation using open source CFD codes. This paper presents numerical analysis of vortex formation in a high head Francis turbine at different operating conditions. Analysis is performed by using OpenFOAM solvers. The κ-ω SST turbulence model is employed in the Reynolds averaged Navier-Stokes’s equations in this study. The computing domain includes the runner and draft tube cone, which is discretized with full three-dimensional mesh system of unstructured tetrahedral shapes. The finite volume method is used to solve the governing equations of mixture model. The tendency of vortex formation in the draft tube cone agrees well with the experimental results with an average deviation of 5.43% in the axial velocity downstream of runner. The nature of vortex is analyzed at different load conditions from 70% of BEP to 117% of BEP.